Initial designs of wheelchair rugby gloves - Bragança, S. (2018)
Wheelchair rugby is a sport played by approximately 200 people in the United Kingdom. Despite being a small part of the population, research suggests that there are some aspects related to the sports-wear that need attention. This is especially relevant for gloves, as they have been identified as one of the main causes of performance losses. Until now, there are no gloves available on the market that were developed to respond to this sport's needs and requirements. The purpose of this paper was to present the concepts of the initial designs and first prototype of a pair of gloves created for wheelchair rugby. The designs were developed based on the feedback from one UK-based wheelchair rugby team. Of the designs produced only one was selected to be developed as a physical prototype. This particular design had in consideration the most important features identified by the athletes, namely the easiness of putting on and taking off the gloves, the padding and grip in specific areas and the elimination of the need for tape to secure.